Therapeutic strategies based on non-ionizing radiation to prevent venous neointimal hyperplasia: the relevance for stenosed arteriovenous fistula, and the role of vascular compliance - Russu, Eliza; Arbanasi, Emil-Marian; Chirila, Traian V.; Muresan, Adrian V. (Frontiers in Cardiovascular Medicine, 2024)
We have reviewed the development and current status of therapies based on exposure to non-ionizing radiation (with a photon energy less than 10 eV) aimed at suppressing the venous neointimal hyperplasia, and consequentially at avoiding stenosis in arteriovenous grafts. Due to the drawbacks associated with the medical use of ionizing radiation, prominently the radiation-induced cardiovascular disease, the availability of procedures using non-ionizing radiation is becoming a noteworthy objective for the current research. Further, the focus of the review was the use of such procedures for improving the vascular access function and assuring the clinical success of arteriovenous fistulae in hemodialysis patients. Following a brief discussion of the physical principles underlying radiotherapy, the current methods based on non-ionizing radiation, either in use or under development, were described in detail. There are currently five such techniques, including photodynamic therapy (PDT), far-infrared therapy, photochemical tissue passivation (PTP), Alucent vascular scaffolding, and adventitial photocrosslinking. The last three are contingent on the mechanical stiffening achievable by the exogenous photochemical crosslinking of tissular collagen, a process that leads to the decrease of venous compliance. As there are conflicting opinions on the role of compliance mismatch between arterial and venous conduits in a graft, this aspect was also considered in our review.